2018
DOI: 10.1038/ajg.2017.430
|View full text |Cite
|
Sign up to set email alerts
|

“Weekend Effect” in Patients With Upper Gastrointestinal Hemorrhage: A Systematic Review and Meta-analysis

Abstract: Current evidence suggests that weekend admission is associated with significant increase in mortality in patients with non-variceal UGIH but no difference in mortality was noted in patients with variceal UGIH. Our findings are relevant to policymakers, practitioners and providers who should ensure the creation of consistent quality and access to care throughout the week.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 47 publications
2
29
1
1
Order By: Relevance
“…A meta-analysis [16] reported that off-hours admission was significantly associated with an increased mortality and less timely endoscopy in patients with nonvariceal bleeding but not those with variceal bleeding. More recently, another meta-analysis [17] also had similar results. However, there were some limitations in previous studies.…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…A meta-analysis [16] reported that off-hours admission was significantly associated with an increased mortality and less timely endoscopy in patients with nonvariceal bleeding but not those with variceal bleeding. More recently, another meta-analysis [17] also had similar results. However, there were some limitations in previous studies.…”
Section: Introductionmentioning
confidence: 53%
“…Two of the published meta-analyses [16, 17] demonstrated a significant weekend effect on the mortality in patients with nonvariceal UGIB, but not those with variceal bleeding. This finding seemed to be consistent with our results regarding mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even with conditions associated with adverse weekend effects, conflicting outcomes have been reported13–15 16–19 and similarly to medical presentations, surgical and intensive care unit (ICU) studies have conflicting results 9 10 20–32. These findings suggest that adverse weekend effects are complex, disease specific and may have different underlying causes including service structure 19. Despite this, a recent assessment of the impact of enhanced 7-day working practices in the UK did not show a beneficial impact on adverse weekend outcomes 33…”
Section: Introductionmentioning
confidence: 99%
“…Transfer status on the weekend for emergent cases like abdominal aortic aneurysm rupture may be associated with higher mortality than weekday transfers. 13 Inconsistency in quality and access to care on the weekends 14 and acute changes in patient status occurring on weekends requiring procedural intervention 15 have been proposed mechanisms for this weekend effect. For ALI, these processes may also contribute to differential patient outcomes.…”
Section: Introductionmentioning
confidence: 99%